Extending School Gardening Programs in Elementary Education: A Phenomenological Study of Experiential Learning - Arezoo Amiri; Shahpar Geravandi; Farahnaz Rostami (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2026)
School gardening programs have gained increasing attention as experiential learning approaches in elementary education, yet empirical evidence from developing-country contexts remains limited. This study explores the educational benefits and implementation challenges of a pilot school gardening program in an urban elementary school in Iran, drawing on social cognitive and socio-cultural learning perspectives. Using a qualitative phenomenological design, the researchers conducted semi-structured interviews with sixty-two stakeholders, including education experts, teachers, school managers, parents, and students. The researchers analyzed the data using Colaizzi’s descriptive phenomenological method to capture participants’ lived experiences. The findings indicate that school gardening programs foster students’ behavioral and psychological development, environmental awareness, collaborative learning, nutritional understanding, and experiential skill acquisition. However, institutional and structural constraints, including bureaucratic regulations, calendar misalignment, limited resources, and stakeholder resistance, continue to challenge effective implementation. This study contributes to the literature by conceptualizing school gardening as an experiential learning ecosystem and by providing context-sensitive insights to inform educational practice and policy in elementary education.